The Effect of Screen Time on Mental Emotional Disorders in Elementary School-Age Children - Ramadhan, Fidia Safa; Ayuningtyas, Putri Rokhima; Ratnawati, Ratnawati (International Journal of Human and Health Sciences (IJHHS), 2025)
Emotional mental disorders refer to conditions in which children experience drastic emotional changes and instability that can affect their development and relationships with their environment. These disorders can be influenced by various factors, including high screen time. This study endeavors to examine the influence of screen time on emotional mental disorders among students in the sixth grade. The research utilized an analytical observational design with a cross-sectional approach. The sample consisted of 49 6th-grade students from SD Islam Sultan Agung 04 Semarang, selected using proportionate random sampling and meeting inclusion criteria (willingness to complete the questionnaire). The instruments used were the Strength and Difficulties Questionnaire (SDQ) and a Screen Time Questionnaire. Data analysis involved Chi-square and Fisher Exact tests. Regarding emotional mental disorder scores (difficulties), the majority of children (57.1%) fell within the normal category. For emotional mental disorder scores (strength), most children (98%) were categorized as normal. In terms of screen time scores, the highest category was high screen time, comprising 35 children (71.4%). The effect of screen time on emotional mental disorders in the difficulties domain yielded a p-value of 0.108 (p > 0.05), while for the strength domain, it was 1.00 (p > 0.05). In conclusion, the study found no significant effect of screen time on emotional mental disorders among the children studied. International Journal of Human and Health Sciences Vol. 09 No. 01 Jan’25 Page: 29-32